Risk of ARI among Non-exclusively Breastfed Under-Five Passive Smoker Children: A Hospital-Based Cross-sectional Study of Nepal - Thapa, Pushpa; Pandey, Achyut Raj; Dhungana, Raja Ram; Bista, Bihungum; Thapa, Barsha; Mishra, Shiva Raj (Frontiers in Public Health, 2016)
Background As Nepal witnesses high burden of both acute respiratory infection (ARI) and passive smoking among under-five children, studies on effect modification of exclusive breastfeeding on passive smoking and ARI carry huge significance. With Nepal holding no evidence in this regard, findings would be useful to promote a cost-effective intervention: exclusive breastfeeding. This study was therefore conceived as an effort to bring to light the modifying effect that exclusive breastfeeding may have on the association between household passive smoking and ARI among under-five children. Methods One hundred and ninety-eight parents of under-five children from Kanti Children’s Hospital, Kathmandu, Nepal, participated in this descriptive, cross-sectional study carried out in October 2012. Data collected from a semi-structured questionnaire were subjected to univariate, bivariate, and multivariable analysis in R version 3.1.2. Results Non-exclusively breastfed children with presence of anyone smoking at their house [aOR = 4.8, 95% confidence interval (CI): 1.7–13.2] and smoking in presence of children (aOR = 6.4, 95% CI: 1.1–38.3) had higher chances of ARI; nevertheless, this remained insignificant among the exclusively breastfed ones. Having a separate kitchen in the house showed protective effect against ARI among exclusively breastfed children (aOR = 0.2, 95% CI: 0.1–0.6). Children whose mothers spent at least 2 h per day in the kitchen had a higher chance of developing ARI, regardless of being exclusively breastfed (aOR = 4.5, 95% CI: 1.5–13.1) or non-exclusively breastfed (aOR = 4.5, 95% CI: 1.4–14.2) compared to those who spent <2 h per day. Conclusion Non-exclusive breastfeeding may increase the chances of deleterious effects of household passive smoking, such as ARI, among under-five children. As these findings are not conclusive, studies with better design and larger samples are warranted to confirm the effect.